If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7x + 5) + -2(3x + -6) + 4 + 36 + 8 = 0 Reorder the terms: 4(5 + 7x) + -2(3x + -6) + 4 + 36 + 8 = 0 (5 * 4 + 7x * 4) + -2(3x + -6) + 4 + 36 + 8 = 0 (20 + 28x) + -2(3x + -6) + 4 + 36 + 8 = 0 Reorder the terms: 20 + 28x + -2(-6 + 3x) + 4 + 36 + 8 = 0 20 + 28x + (-6 * -2 + 3x * -2) + 4 + 36 + 8 = 0 20 + 28x + (12 + -6x) + 4 + 36 + 8 = 0 Reorder the terms: 20 + 12 + 4 + 36 + 8 + 28x + -6x = 0 Combine like terms: 20 + 12 = 32 32 + 4 + 36 + 8 + 28x + -6x = 0 Combine like terms: 32 + 4 = 36 36 + 36 + 8 + 28x + -6x = 0 Combine like terms: 36 + 36 = 72 72 + 8 + 28x + -6x = 0 Combine like terms: 72 + 8 = 80 80 + 28x + -6x = 0 Combine like terms: 28x + -6x = 22x 80 + 22x = 0 Solving 80 + 22x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-80' to each side of the equation. 80 + -80 + 22x = 0 + -80 Combine like terms: 80 + -80 = 0 0 + 22x = 0 + -80 22x = 0 + -80 Combine like terms: 0 + -80 = -80 22x = -80 Divide each side by '22'. x = -3.636363636 Simplifying x = -3.636363636
| -v^2+1v+24=0 | | 4(7x+5)-2(3x-6)= | | 5x-11=2x+2 | | 6n-10=2n-7 | | 5x+2x-3=11 | | mx^2+(m^2+3)x+3m=0 | | 7x-7=4x+17 | | 10x+8=2x+24 | | -3(5x-2)-2(3x+1)= | | x^2-5x-118=0 | | ln(2x-3)+ln(x-2)=2lnx | | 2y^2+9y-5=0 | | x+x-39=375 | | 12y+8=32 | | 2x+500=5x | | 3(5-2b)-4b= | | 0=x^2+12x+3 | | 40-2x=6x+12 | | x^2-8x-8y-24=0 | | -12p-3(5-6p)=2(p-3)-37 | | 5(6+y)-2= | | 3x+500=5x | | 5+y=13-2(y+1) | | 11x+15x-8+5=-8+5-8 | | 10x-5y=100 | | 3.1(7x-0.3)= | | 2-3z=14 | | 5w^2+13w+6=0 | | 7x=10x-450.000 | | 7x=11x-36 | | 4(5y-6)= | | 7(y-8)=-3(6+y) |